Pengaruh Brand Image dan Celebrity Endorser Terhadap Keputusan Pembelian Skincare Skintific dengan Minat Beli Sebagai Variabel Intervening - Cika Yanuari; Edy Purwo Saputro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of brand image and celebrity endorsers on the purchase decision of Skintific skincare, with purchase intention as an intervening variable. The research employs a quantitative approach, collecting data through questionnaires using a five-point Likert scale. Data were analyzed using SEM-PLS with SmartPLS 3.0 software. The respondents consisted of 115 students from Universitas Muhammadiyah Surakarta who have used or purchased Skintific products. The results show that brand image has a positive and significant effect on purchase decisions, with purchase intention as an intervening variable, while celebrity endorsers have a positive but not significant effect on purchase decisions, with purchase intention as an intervening variable.